2010
DOI: 10.1063/1.3463435
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence driven magnetic reconnection causing long-wavelength magnetic islands

Abstract: Magnetic reconnection caused by turbulence in a current sheet is studied by means of numerical simulations of fluid equations. It is found that turbulence produces long-wavelength magnetic islands even if the current sheet is so thick that spontaneous magnetic reconnection does not occur. Thus, turbulence modifies the threshold of magnetic island formation predicted by the conventional theory of spontaneous magnetic reconnection in a current sheet. In spite of the fact that the turbulence is driven by a short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…The detailed modeling of the anomalous effects is still an open issue. 43 Therefore, we treat these coefficients as phenomenological parameters. In addition, the neoclassical thermal transport is not considered, since that is typically smaller than the anomalous perpendicular thermal transport.…”
Section: Basic Model a Two-fluid Model With Neoclassical Viscositymentioning
confidence: 99%
“…The detailed modeling of the anomalous effects is still an open issue. 43 Therefore, we treat these coefficients as phenomenological parameters. In addition, the neoclassical thermal transport is not considered, since that is typically smaller than the anomalous perpendicular thermal transport.…”
Section: Basic Model a Two-fluid Model With Neoclassical Viscositymentioning
confidence: 99%
“…The model used here is a reduced set of two-fluid equations. 18,35 The model consists a set of equations that describes temporal evolutions of the electrostatic potential U, the density n, the parallel ion velocity v k , and the ion temperature T i . In keeping with our electrostatic approach, we neglect the rate of growth of the island in the electron parallel momentum equation (Ohm's law).…”
Section: A Formulationmentioning
confidence: 99%
“…16,17 More recently, two of us have demonstrated a third mechanism whereby ion temperaturegradient turbulence can robustly give rise to magnetic islands of size several times the ion Larmor radius, which may be sufficient to initiate NTM growth. 18 These islands are created by a process of merging, through inverse cascade, of the much smaller-scale magnetic islands that are formed as a by-product of ion temperature gradient driven (ITG) turbulence in finitebeta plasma. The possible existence of additional phenomena related to the interaction of turbulence and magnetic islands, 19 and the relative importance of the three proposed mechanisms are the subject of ongoing research.…”
Section: Introduction a Motivationmentioning
confidence: 99%
“…Both the 3/2 and 2/1 NTM 21,22 have been seen to grow without the existence of an MHD triggering event. The possibility of a turbulence triggered NTM onset has been suggested in the past 14,15,23,24 but remains to some extent an open question to date. It has been shown, in numerical simulations, that small scale interchange turbulence can generate a turbulence driven magnetic island (TDMI), either by a simple mode beating mechanism in the vicinity of a low order rational surface 15 or remotely by spatial transfer of energy of turbulent modes to the lowest available low order rational surface.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous research has identified several different causes for the formation of seed islands such as an unstable tearing mode, [5][6][7] MHD events such as sawtooth 8 and fishbones, 9 error fields, 10,11 edge localized modes (ELMS), 12 nonlinear mode coupling, 13 and turbulence. 14,15 This diversity of origins poses serious challenges for experimentally anticipating their appearance and choosing appropriate control parameters for their avoidance and suppression. 4 Present experimental efforts towards the control of NTMs rely primarily on tracking the appearance of seed islands at various mode rational surfaces and preventing their growth by replacing the missing bootstrap current inside them through externally driven helical currents.…”
Section: Introductionmentioning
confidence: 99%